Postoperative 24-h Acute Sleep Deprivation Improves Learning and Memory Through Inhibition of Tau Phosphorylation in the Hippocampal Neurons of Splenectomized Rats - Zhang Y (Dove Medical Press, 2020)
Yu-wei Zhang,1,2 Xiao-qian Li,1 Wen-fei Tan,1 Bo Fang,1 Hong Ma1 1Department of Anesthesiology, The First Hospital of China Medical University, Shenyang, People’s Republic of China; 2Department of Anesthesiology, The First Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of ChinaCorrespondence: Wen-fei Tan Email winfieldtan@hotmail.comPurpose: As tau pathology is involved in impaired postoperative learning and memory in rats, we attempted to identify the possible mechanisms by which tau pathology affects postoperative sleep deprivation.Methods: Adult male Sprague-Dawley rats were randomly assigned into six groups as follows: the Control group, Anaesthesia group, Surgery group, Sleep deprivation (SD) group: 24-h SD with the modified multiple platform method (MMPM), Anaesthesia and SD (ASD) group, and Surgery and SD (SSD) group. Tau396 and FOXQ1 protein expression levels in the hippocampal neurons of all groups were analysed. Changes following co-culture of hippocampal neurons with IL-6 were detected by flow cytometry.Results: Twenty-four hours of acute SD decreased the error scores on postoperative day 5 in the ASD and SSD groups compared with the Anaesthesia and Surgery groups. Compared with the tau levels in the Control group, tau levels in the Anaesthesia and Surgery groups were increased, but SD decreased the expression of tau in the ASD and SSD groups. The expression levels of tau and FOXQ1 were inversely regulated. When hippocampal neurons were co-cultured with IL-6, the same changes were observed.Conclusion: Postoperative 24-h acute SD improves learning and memory through inhibition of tau phosphorylation and increases IL-6-induced expression of FOXQ1 in the hippocampal neurons of splenectomized rats.Keywords: tau pathology, interleukin-6, postoperative sleep deprivation, FOXQ1, learning, memory